2022
DOI: 10.3390/jpm12030330
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Screening Algorithms for Familial Hypercholesterolaemia in Primary Care

Abstract: Although familial hypercholesterolemia (FH) screening within primary care is considered cost-effective, which screening approach is cost-effective has not been established. This study determines the cost-effectiveness of six case-finding strategies for screening of electronic health records to identify index patients who have genetically confirmed monogenic FH in English primary care. A decision tree was constructed to represent pathways of care for each approach (FH Case Identification Tool (FAMCAT) versions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Of the 21 included studies, five studies were set in Australia [ 20 , 21 , 22 , 23 ], four in the UK [ 24 , 25 , 26 , 27 ], three in the Netherlands [ 19 , 28 , 29 ], two in England and Wales [ 18 , 30 ], two in Spain [ 31 , 32 ], two in the USA [ 33 , 34 ], one in Poland [ 35 ], one in Argentina [ 36 ], and one in Canada [ 37 ]. All the studies were reported in English.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 included studies, five studies were set in Australia [ 20 , 21 , 22 , 23 ], four in the UK [ 24 , 25 , 26 , 27 ], three in the Netherlands [ 19 , 28 , 29 ], two in England and Wales [ 18 , 30 ], two in Spain [ 31 , 32 ], two in the USA [ 33 , 34 ], one in Poland [ 35 ], one in Argentina [ 36 ], and one in Canada [ 37 ]. All the studies were reported in English.…”
Section: Resultsmentioning
confidence: 99%
“…We estimate that screening of all eligible adult healthcare records in this age-bracket would yield 24,564 index cases. In a follow-on from the same study, it was estimated that the incremental cost effectiveness ratio (ICER) for FAMCAT2 versus no active screening was £7,552 [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…We estimate that screening of all eligible adult healthcare records in this age-bracket would yield 24,564 index cases. In a followon from the same study, it was estimated that the incremental cost effectiveness ratio (ICER) for FAMCAT2 versus no active screening was £7,552 [37].…”
Section: Screening Programme Comparisonsmentioning
confidence: 99%